THE PROBLEM OF VERBALIZATION OF EMOTIONS IN THE LANGUAGE OF MORALITY: LINGUISTIC AND PHILOSOPHICAL ASPECTS - Abramova , Anastasiya; Aleshina , Oksana; Gel’fond , Mariya; Mishchuk, Oksana; Miroshina, Evgenia (Revista Inclusiones, 2020)
General linguistic turn in the philosophy of the XX th century provoked a thorough research interest in the peculiarities of the language of morality. In this heuristic context, there is a dominant tendency in modern philosophical discourse to refer to the language as to a phenomenon of being, and, in particular, moral being which is the subject of ethical knowledge. The nature of morality determines and constitutes significant difficulties for its verbal expression and categorical understanding in language constructions. However, the problem of the language of morality is not only to find an adequate linguistic form to express the imperative-evaluative content of a moral judgment, but also to understand which descriptive language (metalanguage) is the most acceptable for the interpretation of moral judgments. The criteria of this choice are the subject for a thorough analysis by various areas of the philosophical thought, logic, linguistics and psychology, which is the reason for the interdisciplinary research approach of the authors.